2009
DOI: 10.1164/rccm.200905-0671oc
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exposure to Intermittent Hypoxia on Oxidative Stress and Acute Hypoxic Ventilatory Response in Humans

Abstract: Chronic intermittent hypoxia increases oxidative stress by increasing production of reactive oxygen species without a compensatory increase in antioxidant activity. This human study shows that reactive oxygen species overproduction modulates increased AHVR. These mechanisms may be responsible for increased AHVR in patients with obstructive sleep apnea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
114
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(131 citation statements)
references
References 49 publications
10
114
1
2
Order By: Relevance
“…Interestingly, after 7 and 14 days of CIH, our model induced an increase in both acute isocapnic hypoxic ventilatory response and acute hyperoxic hypercapnic ventilatory response [25]. This was also reported for isocapnic hypoxic ventilatory response after 4 days of waking IH [26]. Moreover, using the same model, FOSTER et al [27] demonstrated changes in cardio-and cerebrovascular responses to acute hypoxia following exposure to intermittent hypoxia.…”
supporting
confidence: 81%
“…Interestingly, after 7 and 14 days of CIH, our model induced an increase in both acute isocapnic hypoxic ventilatory response and acute hyperoxic hypercapnic ventilatory response [25]. This was also reported for isocapnic hypoxic ventilatory response after 4 days of waking IH [26]. Moreover, using the same model, FOSTER et al [27] demonstrated changes in cardio-and cerebrovascular responses to acute hypoxia following exposure to intermittent hypoxia.…”
supporting
confidence: 81%
“…64,65 The increase in inflammatory cytokines is thought to be related to repeated cycles of apneic oxygen desaturation and restoration. 44,[66][67][68][69][70] OSA has been shown to be an inflammatory process, associated with increased levels of systemic interleukin-2, interleukin-6, C-reactive protein, and tumor necrosis factor-alpha .…”
Section: Discussionmentioning
confidence: 99%
“…[77][78][79][80][81][83][84][85][86] Long-term exposure to these recurrent episodes of hypoxiareoxygenation activate nicotinamide adenine dinucleotide phosphate-oxidase 2 that consumes oxygen through its generation of reactive oxygen species. [287][288][289][290][291] Tissue damage effected by these species is augmented by intermittent hypoxia reducing renal expression of antioxidants. 292 In addition, intermittent hypoxia induces the sympathetic nervous system to increase vascular resistance, downregulates expression of the kallikrein-kallistatin vasodilator Shelley Transforming growth factor β inhibition 446 Pro-fibrotic metalloproteinase inhibition 447 Anti-fibrotic metalloproteinase activation 447 Destabilization of renal Remote ischemic pre-conditioning [384][385][386][387][388][389][390] hypoxia-inducible factor Prolyl hydroxylase inhibition 244,448 von Hippel-Lindau protein inhibition 449 pathway, and activates the renal renin-angiotensin-aldosterone system to cause vasoconstriction.…”
Section: Repeated Episodes Of Acute Kidney Injurymentioning
confidence: 99%